2017
DOI: 10.4187/respcare.05210
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Adult Critically Ill Subjects With Cancer

Abstract: The present study failed to show an association between malignancy and all-cause 30-d mortality rate in adult subjects admitted to a mixed medical-surgical ICU. The propensity score-matched analysis showed no evidence of excessive mortality due to cancer diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…In the study, cancer patients in MICU have a higher incidence of organ dysfunction and require more intensive support (such as MV, vasopressors, and RRT), which was consistent with previous literature (20). Patients in SICU Recent advance in anti-cancer treatment has gradually improved the overall survival of patients with metastatic cancer (22,23).…”
Section: Discussionsupporting
confidence: 88%
“…In the study, cancer patients in MICU have a higher incidence of organ dysfunction and require more intensive support (such as MV, vasopressors, and RRT), which was consistent with previous literature (20). Patients in SICU Recent advance in anti-cancer treatment has gradually improved the overall survival of patients with metastatic cancer (22,23).…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, patients with cancer had a greater need for intensive support (eg, MV, vasopressor administration, and RRT), which was consistent with previous literature [24]. In patients with MV support, we found that noncancer patients had survive advantage at the point of 28-day and 90-day after ICU admission.…”
Section: Discussionsupporting
confidence: 91%
“…Unfortunately, in our study 9 we did not compare the mortality rates of patients with solid neoplasms with those with hematological neoplasms, and this remains as an evidence gap due to the scarce literature about this issue. Some studies have shown that subjects with hematological malignancies have higher ICU mortality rates when compared with subjects with solid cancers.…”
Section: Prognosis Of Cancer Patients In the Icu: Much Work Remains-rmentioning
confidence: 94%